Co-responsibility in psychoeducational intervention for older adults: analysis of the joint work between academia, local authorities and the community of Orotina - Madrigal-Chaves, Graciela (2026)
The study focus on the design and validation of a psychoeducational program to provide comprehensive mental healthcare for older adults in Santa Rita, Orotina, Costa Rica. Using the action-participation method within the framework of the World Network of Age-Friendly Cities and Communities model, the research findings reveals that older people in Santa Rita experience psychosocial vulnerability, exacerbated by a lack of professional mental health support at the cantonal level. The macro project for age-friendly cities primarily emphasizes physical and structural aspects, often neglecting critical elements such as psychosocial interactions and socio-affective factors. To address these gaps, protective factors like healthy habits and community support have been incorporated into a guide for facilitating psychoeducational workshops. From a locally-based rural approach, rooted in a rural context, the exploratory implementation not only promotes health for older adults, but also enhances psychological well-being of the alliances of responsibility between civil society, the local government, and the public university.